2014
DOI: 10.1194/jlr.d047795
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced lipid isomer separation in human plasma using reversed-phase UPLC with ion-mobility/high-resolution MS detection

Abstract: This article is available online at http://www.jlr.orgLipids are the building blocks of all cell membranes and are thus essential for various biological functions varying from membrane traffi cking to signal transduction. Disorders in lipid metabolism play a key role in various diseases including cardiovascular disease, cancer, diabetes mellitus, and infl ammation ( 1, 2 ). Lipids have been classifi ed into eight categories (fatty acyls, glycerolipids, glycerophospholipids, sphingolipids, sterol lipids, prenol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
115
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(120 citation statements)
references
References 45 publications
5
115
0
Order By: Relevance
“…n--9 elutes before n--12, Figure 2a). This observation is consistent with previous reports of separation of double bond positional isomers and evidence from new column technologies suggests further improvements in isomer separation can be achieved [17,19,18]. Full structure elucidation of complex lipids however, also requires separation and/or mass spectral differentiation of isomers that differ in (i) the position of acyl chains on the glycerol backbone (i.e., sn--positional isomers) and the stereochemistry about the double bond(s) (i.e., cis and trans).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…n--9 elutes before n--12, Figure 2a). This observation is consistent with previous reports of separation of double bond positional isomers and evidence from new column technologies suggests further improvements in isomer separation can be achieved [17,19,18]. Full structure elucidation of complex lipids however, also requires separation and/or mass spectral differentiation of isomers that differ in (i) the position of acyl chains on the glycerol backbone (i.e., sn--positional isomers) and the stereochemistry about the double bond(s) (i.e., cis and trans).…”
Section: Discussionsupporting
confidence: 92%
“…Prior observation of the behaviour of unsaturated phosphatidylcholines on reversed phase columns suggests that the peaks eluting at 49.0 and 50.4 min correspond to the isomers PC 18:1(n--9)/18:1(n--9) and PC 18:1(n--12)/18:1(n--12), respectively [17,19,18]. Integration of OzID scans obtained across each of the chromatographic peaks gave the OzID mass spectra shown in bonds closer to the methyl terminus of lipid acyl chains has previously been noted [24].…”
Section: [Figure 2]mentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, Damen et al [28] demonstrated the superior separation of different isomers using the CSH (charged surface hybrid) C18 column in comparison with the HSS T3. Despite its bigger particle size (2.6 μm), Accucore C30 column showed higher performance than the other three columns with sub 2 μm particles.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, unsaturated phosphatidylcholines have been separated with TWIMS-MS on the basis of differences in chain length and double bond number/position (67 ). More recently, LC-TWIMS-MS allowed resolution of coeluting lipid isomers in human plasma extracts, showing the potential for this technique to improve clinical LC-MS methods both qualitatively and quantitatively (68 ). Collection of ion mobility-derived CCS values can further improve lipidomics specificity, especially with complex biological samples or when performing MALDI imaging studies that offer no chromatographic separation (69 ).…”
Section: Ion Mobility In Clinical Analysismentioning
confidence: 99%